Study on the Permeability Evolution Model of Mining-Disturbed Coal. (26th August 2021) - Jia, Hengyi; Zou, Delong
Abstract : Coal permeability plays an important role in the simultaneous exploitation of coal and coal-bed methane (CBM). The stress of mining-disturbed coal changes significantly during coal mining activities, causing damage and destruction of the coal mass, ultimately resulting in a sharp increase in permeability. Conventional triaxial compression and permeability tests were conducted on a triaxial creep-seepage-adsorption and desorption experimental device to investigate the permeability evolution of mining-disturbed coal. The permeability evolution models considering the influence of the stress state and stress path on the fracture propagation characteristics were established based on the permeability difference in the deformation stages of the coal mass. The stress-strain curve of the coal was divided into an elastic stage, yield stage, and plastic flow stage. As the axial stress increased, the permeability decreased and then increased, and the curve's inflection point corresponded to the yield point. The permeability models exhibited a good agreement with the experimental data and accurately reflected the overall trends of the test results. The results of this study provide a theoretical basis for coal mine disaster prevention and the simultaneous exploitation of coal and CBM.